Transnational Feminism, Islam, and the Other Woman: How to Teach - Gurel, Perin (Radical Teacher, 2019)
The author argues that “the progressive scholar engaging women’s issues in the Muslim world must strive to do three things: historicize feminism, historicize Islam, and highlight the complexities of representation” – and she explains how.